2012
DOI: 10.1029/2012gl051199
|View full text |Cite
|
Sign up to set email alerts
|

Crustal thickness and earthquake distribution south of the Logachev Seamount, Knipovich Ridge

Abstract: During RV Polarstern cruise ARK‐XXIV/3 (2009), a geophysical study along the ultraslow spreading Knipovich Ridge was conducted. The survey, located in the rift valley south of the Logachev Seamount (∼76°36′N), provides a crustal thickness of ∼4.5 km in the amagmatic parts and 5.7 km underneath the seamount itself. The velocity‐depth function indicates the presence of a thick oceanic layer 2 (4.5 km), but no indication for a thick oceanic layer 3. The only exception is the area underneath the Logachev Seamount,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 38 publications
6
32
0
Order By: Relevance
“…The most significant difference as compared to previously studied ultraslow‐spreading segments [e.g., Jokat et al , ; Minshull et al , ; Zhao et al , ] is the presence of a much thicker crust and the crustal magma system, both indicating an excess melt supply to this segment that has been persistent for more than 3 Ma [ Li et al , ]. In addition, the maximum crustal thickness beneath the segment center (∼9.5 km) is even larger than those at the slow‐spreading MAR segments that also contain similar lower crustal magma chambers [ Seher et al , ; Dunn et al , ].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The most significant difference as compared to previously studied ultraslow‐spreading segments [e.g., Jokat et al , ; Minshull et al , ; Zhao et al , ] is the presence of a much thicker crust and the crustal magma system, both indicating an excess melt supply to this segment that has been persistent for more than 3 Ma [ Li et al , ]. In addition, the maximum crustal thickness beneath the segment center (∼9.5 km) is even larger than those at the slow‐spreading MAR segments that also contain similar lower crustal magma chambers [ Seher et al , ; Dunn et al , ].…”
Section: Discussionmentioning
confidence: 78%
“…A general way is to generate a 1‐D starting model from previous studies in the same area or similar areas [ Seher et al , ]. However, the gravimetric observations [ Sauter et al , ] at this study area suggest that the crustal thickness is more than the global average of ∼6 km [ Chen , ], much larger than any other seismically studied segments at ultraslow‐spreading ridges [ Jokat et al , ; Minshull et al , ]. As the morphology shows a similarity to the slow‐spreading segments, we first constructed a velocity‐depth profile similar to the MAR type velocity profiles at segment centers [ Canales et al , ; Hooft et al , ; Seher et al , ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One-dimensional velocity model. To derive a minimum one-dimensional velocitydepth profile, as commonly used in earthquake location 33 , we used the results of refraction seismic surveys 15,34,35 conducted within each of the study sites (Extended Data Figs 1a, 2a and 3a). We extracted smoothed average velocity-depth profiles for the upper 5 km, where the refraction seismic data provided sufficient ray cover.…”
Section: Methodsmentioning
confidence: 99%
“…A brief microseismicity study at SWIR volcano 11 (Fig. 11;Yamada et al 2002) suggested hypocentres depths up to 8 km below the seafloor, while a more comprehensive microseismicity study on the Knipovich ridge found maximum hypocentral depths c. 20 km beneath the axial basins, and c. 8 km beneath the volcanic centres (Jokat et al 2012;Schlindwein et al 2013). The results for axial basins suggest a brittle lithospheric thickness in excess of the 8 -10 km that is typically inferred from hypocentre depths at the MAR (Toomey et al 1988;Wolfe et al 1995;de Martin et al 2007).…”
mentioning
confidence: 99%